Determinants of choice of private hospital by consumers in Malaysia - Nasrijal, Neliza Hilmy (2002)
The health care industry in Malaysia has grown tremendously over this decade through the existence of private hospitals particularly in Klang Valley. It has become a trend or in fact a necessity for consumers to seek treatment at private hospitals. With the changes of this industry, hospital administrators and marketers are faced with enormous challenges due to the skyrocketed costs, fierce competition and the variety of choice available to consumers. This study intended to understand the uniqueness of consumers in health care settings particularly private hospital. Its main objective is to identify the important determinants that influence consumers' choice behavior when selecting their preferred private hospitals. Analytical Hierarchy Process developed by Saaty (1977,1980) a framework and measurement system designed to analyze complex decision was featured to predict health care choice decisions. The research design comprises of focus group and survey. 300 self-administered questionnaires were circulated to respondents residing in the selected private hospital areas and the patients of the hospitals itself. Only 235 responded and 220 were used in the analysis indicating 73.3% of response rate. Nine criterion of consumer choice from the input of focus group as well as literature reviews were used in the interpretation of AHP to identify the rank of importance amongst them. "Near to home", "reasonable cost" and "excellent and prompt service" were the first three important criteria in the findings. Based on the global priority of the criterion Subang Jaya Medical Centre is preferred private hospital. The criterion is recommended to be a tool in developing marketing strategies for hospital marketers as it can be categorized into the marketing mix of 7Ps. The AHP is recommended to study other consumer decision process in similar choice problems particularly in health care marketing.